Regenerative Drug Discovery Using Ear Pinna Punch Wound Model in Mice - Paweł Sosnowski; Piotr Sass; Paulina Słonimska; Rafał Płatek; Jolanta Kamińska; Jakub Baczyński Keller; Piotr Mucha; Grażyna Peszyńska-Sularz; Artur Czupryn; Michał Pikuła; Arkadiusz Piotrowski; Łukasz Janus; et al. (MDPI AG, 2022)
The ear pinna is a complex tissue consisting of the dermis, cartilage, muscles, vessels, and nerves. Ear pinna healing is a model of regeneration in mammals. In some mammals, including rabbits, punch wounds in the ear pinna close spontaneously; in common-use laboratory mice, they remain for life. Agents inducing ear pinna healing are potential regenerative drugs. We tested the effects of selected bioactive agents on 2 mm ear pinna wound closure in BALB/c mice. Our previous research demonstrated that a DNA methyltransferase inhibitor, zebularine, remarkably induced ear pinna regeneration. Although experiments with two other demethylating agents, RG108 and hydralazine, were unsuccessful, a histone deacetylase inhibitor, valproic acid, was another epigenetic agent found to increase ear hole closure. In addition, we identified a pro-regenerative activity of 4-ketoretinoic acid, a retinoic acid metabolite. Attempts to counteract the regenerative effects of the demethylating agent zebularine, with folates as methyl donors, failed. Surprisingly, a high dose of methionine, another methyl donor, promoted ear hole closure. Moreover, we showed that the regenerated areas of ear pinna were supplied with nerve fibre networks and blood vessels. The ear punch model proved helpful in testing the pro-regenerative activities of small-molecule compounds and observations of peripheral nerve regeneration.